Optimizing Evaluation of Older Adults With Vision and/or Hearing Loss Using the interRAI Community Health Assessment and Deafblind Supplement - Urqueta Alfaro, Andrea; McGraw, Cathy; Guthrie, Dawn M.; Wittich, Walter (Frontiers in Rehabilitation Sciences, 2021)
Purpose: Service providers must identify and assess older adults who have concurrent vision and hearing loss, or dual sensory impairment (DSI). An assessment tool suitable for this purpose is the interRAI Community Health Assessment (CHA) and its Deafblind Supplement. This study’s goal was to explore this assessment’s administration process and to generate suggestions for assessors to help them optimize data collection. Methods: A social worker with experience working with adults who have sensory loss, who was also naïve to the interRAI CHA, administered the assessment with 200 older adults (65+) who had visual and/or hearing loss. The assessor evaluated the utility of the instrument for clinical purposes, focusing on sections relevant to identifying/characterizing adults with DSI. Results: Suggestions include the recommendation to ask additional questions regarding the person’s functional abilities. This will help assessors deepen their understanding of the person’s sensory status. Recommendations are also provided regarding sensory impairments and rehabilitation, in a general sense, to help assessors administer the interRAI CHA. Conclusions: Suggestions will help assessors to deepen their knowledge about sensory loss and comprehensively understand the assessment’s questions, thereby allowing them to optimize the assessment process and increase their awareness of sensory loss in older adults.